Snowy with a chance of murder - Fletcher, Jessica; Early, Barbara (Fletcher, Jessica. Murder, she wrote., 2025)
"In a nod to Rear Window, this newest entry in the USA Today bestselling Murder, She Wrote series finds Jessica Fletcher coping with an injury that leaves her homebound--and a murder just outside her window! Jessica Fletcher has taken a nasty spill on the ice, leaving her in a wheelchair for several weeks. She tries to work on her latest manuscript but finds herself distracted by a new neighbor moving in across the street. There's good reason for her to be distracted, because soon after unpacking his sparse belongings, Mr. Rymer is out in the front yard, building somewhat risqué (read: naked) snow sculptures. While Cabot Cove debates whether the sculptures are a protected form of art or a public display of lewdness, someone starts destroying them at night. Rymer doesn't seem upset. He just makes new ones. No need to get the police involved over a little snow, he says. Especially when there's plenty more of it and a blizzard in the forecast. The morning after the storm, Jessica looks out the window to see a new sculpture across the street--and the body of Mr. Rymer half-buried in the snow. Can Jessica catch a cold-blooded killer from her chair by the window?"--